Papillary carcinoma of the thyroglossal cyst as a metastasis of microcarcinoma of thyroid cancer: a case report and literature review - Franzi, Sergio Altino; Souza, Tania Regina de Bastos (Brazilian Journal of Oncology, 2021)
Papillary carcinoma of the thyroglossal cyst is clinically like the benign lesion in adults aged 15-45 year, with a higher incidence in females. It is a congenital anomaly of the midline of the neck and have the clinical worsening related to infections of high aerodigestive routes. We discuss clinical assess, diagnosis, surgery, hormonal suppression, radioiodine therapy, and prognosis in a patient with a complaint of nodule in the neck, and to the ultrasonography an image suggestive of the thyroglossal cyst without alteration of thyroid gland. He was submitted to Sistrunk's surgery and the anatomopathological exam revealed papillary carcinoma, and we do not find normal thyroid follicles in the thyroglossal cyst wall. We perform the total thyroidectomy by the thyroid alterations, showing in the anatomopathological exam a thyroid microcarcinoma. We completed by hormonal suppression and radioiodine therapy. The prognosis is favorable and the patient presented asymptomatic until now.
Keywords: Thyroglossal cyst; Thyroid Cancer; Papillary; Diagnosis; Combined modality therapy.